The Concept of Legal Protection for Children Victims of Sexual Crimes in the Perspective of Islamic Law - Kurniawan, Harry (Jurnal Ilmiah Teunuleh, 2025)
Sexual crimes against children are serious violations of human rights and dignity that have long-term physical, psychological, and social impacts. In this context, legal protection of children is an urgent imperative. This study aims to analyze the concept of legal protection for children victims of sexual crimes from the perspective of Islamic law, as well as its relevance to the national legal system in Indonesia. The method used is qualitative research with a normative-juridical approach through literature studies on fiqh literature, the Qur’an, hadith, and laws and regulations. The results of the study show that the principles of Islamic law contained in maq??id al-syar?’ah, such as the protection of the soul (?if? al-nafs), reason (?if? al-’aql), and heredity (?if? al-nasl), expressly emphasize the protection of children from sexual crimes. In addition, the Islamic legal system is not only repressive against the perpetrators, but also emphasizes restoration and justice for the victims. This study concludes that the integration of Islamic legal principles into the national legal system can strengthen child protection in a holistic and equitable manner.